Simulated Seismic Damage Evolution in Concrete Shear Walls - Faraone, Gloria; Hutchinson, Tara C; Piccinin, Roberto; Silva, John F (ACI structural journal, 2023)
Robust numerical representation of the behavior of reinforced concrete (RC) shear walls under simulated earthquake action is critical to support an accurate evaluation of the performance of concrete buildings. Reliable damage predictions of concrete shear walls are also essential to understand the response of components attached to walls via anchors. Previous studies have shown that anchor load capacity is reduced in the presence of concrete damage. Accordingly, current U.S. building code requirements prohibit anchor installation in sections of walls where yielding of the reinforcement is expected. The aim of this requirement is to minimize the potential for anchorage failure during a seismic event. Identification of concrete damage in shear walls of varying characteristics is therefore relevant to anchor performance. In this regard, the present paper describes a parametric study performed using a multiple vertical-line element model able to couple shear-flexure interaction. The aim of the study is to qualitatively identify regions of severe damage in concrete shear walls of varied geometric and detailing characteristics and thus better assist engineers in adhering with current code requirements. Results show that the regions where large damage is expected define a plastic hinge length and include the boundary elements in slender walls and the diagonal compression struts in squat walls. This information is used to suggest anchor installation locations to assure their robust performance when attaching nonstructural components and systems to RC shear walls subject to seismic loading.